Hubungan Antara Pemahaman Konsep dan Kemampuan Berpikir Kritis Siswa dalam Pembelajaran Matematika di Sekolah Dasar: Suatu Kajian Sistematis Literatur - Muhammad Arifin (GENFABET: Generasi Pendidikan Dasar, 2025)
This study aims to systematically examine the relationship between conceptual understanding and critical thinking skills in elementary school students during mathematics learning. A Systematic Literature Review (SLR) was conducted using the PRISMA protocol. A total of 32 relevant journal articles published between 2006 and 2024 were selected from databases such as Google Scholar, Scopus, DOAJ, and ResearchGate. Mendeley was used for reference management and NVivo 12 Plus was employed for thematic coding and qualitative synthesis. The review reveals a significant relationship between students’ conceptual understanding and their critical thinking abilities, especially when real-world, contextual problem-solving activities are applied. Strategies such as Problem-Based Learning (PBL), inquiry-based instruction, visual media, and metacognitive approaches were consistently effective in strengthening both skills. Contextual and reflective learning environments further support the development of integrated cognitive competencies. Despite these findings, gaps remain in long-term experimental studies and in understanding the mediating role of visual learning tools. This study provides theoretical insights and practical implications for improving mathematics instruction in elementary education.